Designing and Cloning of the Gene Sequence Encoding Silk Fibroin Amorphous Domain - 黄海燕 田智芳 裔洪根 杨云星 王建南 (东华大学学报（英文版）, 2012)
To provide materials used in investigating the relationship between amino acid compositions of silk-like protein, structure, and functions, especially the biological functions, the motif genes encoding the silk fibroin amorphous domain, SGFGPVANGGSGEASSESDFGSSGFGPVANASSGEASSESDFAG （F） were designed and extended using a ＂head-to-tail＂ construction strategy. The designed genes were cloned into PSLFA1180FA and multimerized to form structures containing a two-timer, a four- timer, an eight-timer, and a twelve-timer. All the resulting plasmids were digested using the restriction enzyme BamI-II and the double- enzymes BgllL/HindHI. Restriction enzyme analysis and DNA sequencing revealed the motif was successfully cloned into PSLFAll80FA and mnitimerized to form a twelve-timer without eene deletion or mutation.